Pharmacoepidemiological study of self-medication in adultsattending pharmacies in Tikrit city, Iraq - Abdul Khalk Yehea Al-Handhl, Ban (Tikrit Journal of Pharmaceutical Sciences, 2023)
A cross-sectional study was conducted to determine the extent and pattern of self medication among adults, to identify their knowledge and practice concerning the purchased drug sand lo calculate prescribing and purchaser care indicators, Following. WHO methods, 30 pharmacies were randomly selected from Tikrit city, Iraq. Of 1000 clients interviewed al these pharmacies, 811 (81.1%) purchased self-medication; the commonest reason given was a belief thal the condition was minor. The most frequently dispensed drugs were those for the respiratory system, The mean number of drugs per encounter was 1.10, mean cost 1500 ID, and mean dispensing time 2.53 minutes. Purchasers’ knowledge and practice regarding the purchased drugs were poor.